Dakwah dan Komunikasi Persuasif Tuan Guru di Lombok dalam Penyampaian Pesan Vaksinasi Covid-19 - Ummah, Athik Hidayatul (Jurnal Dakwah, 2022)
The government of Indonesia has taken some strategies to prevent the spread of Covid-19, one of them is vaccination. In the era of information abundance facilitated by digital media or social media, there is polarization of perceptions and attitudes in the community about the Covid-19 vaccination program policy. Hoaxes and disinformation make people rejection or doubtful about Covid-19 vaccinations. Religious leaders have a significant role in providing explanations and constructing counter-narratives about Covid-19 vaccination. This study aims to explain persuasive communication strategy of the religious leader (“Tuan Guru”) in Lombok with an Islamic da'wah approach. This study is a qualitative research. The method is discourse analysis. The data analyzed from books, scientific journals, news articles and interview transcripts. The results showed that the persuasive da'wah and communication strategy aims to change the beliefs, attitudes and behavior of people who are in latitude of non-commitment groups. This strategy can strengthen discourse or information (as education) for the community, subjective norms and counter-narrative hoaxes about vaccinations on social media. The persuasive da'wah and communication strategy of Tuan Guru in Lombok is carried out through two methods, namely the direct communication method at the recitation forums and creating positive narratives “Ayo Vaksin” in online media and social media.